2008
DOI: 10.1159/000113539
|View full text |Cite
|
Sign up to set email alerts
|

Handedness in Captive Bonobos (Pan paniscus)

Abstract: Species level right-handedness is often considered to be unique to humans. Handedness is held to be interrelated to our language ability and has been used as a means of tracing the evolution of language. Here we examine handedness in 3 captive groups of bonobos (Pan paniscus) comprising 22 individuals. We found no evidence for species level handedness. Conclusions that can be drawn from these findings are: (1) species level handedness evolved after the divergence of the Pan and Homo lineages; (2) inconsistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…Curiously, one study of 22 bonobos, which along with common chimpanzees are our closest living nonhuman relatives, revealed no evidence for species-level handedness (Harrison & Nystrom 2008). Palmer (2002) has suggested that the findings of Hopkins and colleagues may be due to statistical artefacts, and has shown the results to be marginal when assessed using funnel plots, which show scatter plots of righthand use against sample size, although the more recent studies do reveal significant species-level right-handedness using this technique (e.g.…”
Section: Laterality In Non-human Species (A) Handednessmentioning
confidence: 99%
“…Curiously, one study of 22 bonobos, which along with common chimpanzees are our closest living nonhuman relatives, revealed no evidence for species-level handedness (Harrison & Nystrom 2008). Palmer (2002) has suggested that the findings of Hopkins and colleagues may be due to statistical artefacts, and has shown the results to be marginal when assessed using funnel plots, which show scatter plots of righthand use against sample size, although the more recent studies do reveal significant species-level right-handedness using this technique (e.g.…”
Section: Laterality In Non-human Species (A) Handednessmentioning
confidence: 99%
“…~90% right-handed) typical of humans [e.g., Annett, 1972;Raymond and Pontier, 2004;McManus, 2009]. Hand preference or laterality has been investigated in bonobos but almost exclusively in captive groups, and primarily involving unnatural objects and simple tasks such as reaching for food, gesturing or scratching [e.g., De Vleeschouwer et al, 1995;Hopkins and de Waal, 1995;Colell et al, 1995;Harrison and Nystrom, 2008]. In all of these studies, most bonobo individuals were non-lateralized (i.e., used both hands interchangeably) for most of the actions studied.…”
Section: Introductionmentioning
confidence: 99%
“…Research on bonobos (Pan paniscus) has found little evidence for species-level handedness, though population-level handedness has been found for certain tasks, for example leading limb, reaching for food and gesturing (e.g. Hopkins et al 1993b;de Vleeschouwer et al 1995;Hopkins and de Waal 1995;Harrison and Nystrom 2008), and individual preferences have been found during tool use and feeding (Harrison and Nystrom 2008).…”
Section: Introductionmentioning
confidence: 99%